Sox2, Tlx, Gli3, and Her9 converge on Rx2 to define retinal stem cells in vivo - Reinhardt, Robert; Centanin, Lázaro; Tavhelidse-Suck, Tinatini; Inoue, Daigo; Wittbrodt, Beate; Wittbrodt, Joachim (The EMBO journal, 2015)
Transcriptional networks defining stemness in adult neural stem cells (NSCs) are largely unknown. We used the proximal cis ‐regulatory element (pCRE) of the retina‐specific homeobox gene 2 ( rx2 ) to address such a network. Lineage analysis in the fish retina identified rx2 as marker for multipotent NSCs. rx2 ‐positive cells located in the peripheral ciliary marginal zone behave as stem cells for the neuroretina, or the retinal pigmented epithelium. We identified upstream regulators of rx2 interrogating the rx2 pCRE in a trans ‐regulation screen and focused on four TFs (Sox2, Tlx, Gli3, and Her9) activating or repressing rx2 expression. We demonstrated direct interaction of the rx2 pCRE with the four factors in vitro and in vivo . By conditional mosaic gain‐ and loss‐of‐function analyses, we validated the activity of those factors on regulating rx2 transcription and consequently modulating neuroretinal and RPE stem cell features. This becomes obvious by the rx2 ‐mutant phenotypes that together with the data presented above identify rx2 as a transcriptional hub balancing stemness of neuroretinal and RPE stem cells in the adult fish retina.This study establishes Rx2 as functional determinant of neuro‐epithelial progenitor fate and uncovers the gene regulatory network that governs Rx2 expression.
Gesehen am 31.01.2017